Efficacy of spinal fusion in Brucella spondylitis: a systematic review - He, Kai; Xing, Wenhua (Frontiers in Surgery, 2025)
BackgroundBrucellosis affects more than 500,000 people worldwide each year, and brucellosis spondylitis is one of its most common complications, accounting for about 2–53 percent of cases.PurposeThe aim of this study was to systematically review the literature on the outcome of spinal fusion in patients with Borrelia burgdorferi spondylitis.Study designSystematic review.MethodsSeventeen studies including 746 patients treated with minimally invasive and/or open spinal fusion were reviewed. Patients with this pathologic spondylolisthesis showed significant improvement in clinical and functional scores and high satisfaction after spinal fusion. The overall fusion rate was 99%, the excellent fusion rate was 90%, and all patients with fusion devices placed achieved fusion. The Oswestry disability index scores decreased from 62.11 (35.72–88.5) preoperatively to 7.22 (4.0–10.44) postoperatively, the Japanese Orthopaedic Association scores improved from 15.13 (range, 10.47–19.79) preoperatively to 22.17 (16.4–27.93) postoperatively, and the The visual analog scale scores improved from 6.95 (4.5–9.4) to 1.33 (0–2.66) postoperatively, Erythrocyte sedimentation rate from 49.95 (35.5–64.4) preoperatively to 8.17 (4.13–12.2) postoperatively, and C-reactive protein from 41.25 (20.3–62.2) preoperatively to 4.48 (1.25–12.2) postoperatively. In addition, all patients showed varying degrees of neurological improvement, with a probability of complete return to normal neurological symptoms of 88.79%. Spinal deformities also improved significantly.ConclusionSpinal fusion can achieve a high clinical success rate and has a favourable prognosis and pain relief in patients with Brucella spondylitis. Although patients with Brucella spondylitis have a number of high-risk factors affecting the outcome of fusion, in conjunction with medication and debridement, spinal fusion may be a good option with significant functional and clinical improvement.